2007
DOI: 10.1128/jcm.02245-06
|View full text |Cite
|
Sign up to set email alerts
|

Frequent In Vitro Recombination in Internal Transcribed Spacers 1 and 2 during Genotyping of Pneumocystis jirovecii

Abstract: Pneumocystis jirovecii is the causative agent of Pneumocystis pneumonia (PCP) in immunocompromised persons. Knowledge of the transmission and epidemiology of PCP is still incipient, and investigations on these subjects are based exclusively on applications of molecular typing techniques. The polymorphic internal transcribed spacers ITS1 and ITS2 in the ribosomal DNA operon, which in the P. jirovecii genome exist as single-copy DNA, are commonly used as target loci for isolate typing. In the course of genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…That is lower than the frequency we obtained. The reasons could be [16] the length of the fragment they used to detect crossovers of 14 signature nucleotides (RT amino acid positions 181, 184, 188, 190, 210, 215, and 219) is shorter than ours (positions 41, 65, 67, 70, 74, 100, 103, 181, 184, 188, 190, 215, 219) [29]. We have signature nucleotide from positions 41 to 103.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is lower than the frequency we obtained. The reasons could be [16] the length of the fragment they used to detect crossovers of 14 signature nucleotides (RT amino acid positions 181, 184, 188, 190, 210, 215, and 219) is shorter than ours (positions 41, 65, 67, 70, 74, 100, 103, 181, 184, 188, 190, 215, 219) [29]. We have signature nucleotide from positions 41 to 103.…”
Section: Discussionmentioning
confidence: 99%
“…Mild et al [22] used 100,000 templates in PCR and observed 0.89% recombinants while we used 1,000,000 templates in our PCR and observed 11.65% recombinants. PCR mediated recombination results from incompletely extended primers annealing to heterologous templates and extending in the next round of elongation [14,16]. By modifying PCR conditions to reduce the probability of premature termination, we found that that PCR mediated recombination could be reduced by 27 fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper case italics as (␤-TUB), Using DNA extracts from 11 confirmed PJP cases, the ITS1/2, ␤-TUB, ␤-TUB, mtLSU, and DHPS loci were amplified using primers and amplification conditions as specified (see Table, SDC 3, http://links.lww.com/TP/A553) (32)(33)(34)(35). Amplicons were purified and then sequenced commercially (Macrogen Inc., Seoul, Korea).…”
Section: Epidemiological Investigationsmentioning
confidence: 99%
“…Host cell DNA repair system can also produce variants. When the host cell assimilates a plasmid containing heteroduplexes, a mismatch repair system works randomly utilizing either strand as template and thus makes chimeric sequences (Speksnijder et al, 2001;Longeri et al, 2002;Kanagawa, 2003;Beser et al, 2007). These PCR or cloning errors give rise to risks on over-estimation of number of haplotypes or alleles.…”
Section: Introductionmentioning
confidence: 99%